2017
DOI: 10.1158/1055-9965.epi-17-0510
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Status in Adult Survivors of Childhood Cancer: A Report from the St. Jude Lifetime Cohort Study

Abstract: Background Hypertension potentiates cardiovascular risk in survivors of childhood cancer previously exposed to cardiotoxic therapies, so it is important to determine the prevalence and risk factors for hypertensive blood pressure in this high risk group. Methods Participants included 3016 adult 10-year survivors of childhood cancer who had resting blood pressure measurements performed at St. Jude Children’s Research Hospital. We characterized the blood pressure status of participants, calculated standardized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Cardoos-Ubbink et al also demonstrated that BMI is the most important risk factor for hypertension following treatment of childhood cancer, emphasizing the need for cancer survivors to maintain a normal weight, although a recent study on a large number of survivors found that BP was substantially higher in all diagnosis groups than expected on the basis of age-, sex-, race/ethnicity-, and BMI-specific population rates. 22,23 In conclusion, in the present study long-term sarcoma survivors previously treated with ifosfamide as the only nephrotoxic agent do not seem to be at high risk for nephrotoxicity. This finding has not been reported so far, it could be conditioned by the small number of cases, and further studies including a larger number of adult long-term survivors are required.…”
Section: Discussionsupporting
confidence: 46%
“…Cardoos-Ubbink et al also demonstrated that BMI is the most important risk factor for hypertension following treatment of childhood cancer, emphasizing the need for cancer survivors to maintain a normal weight, although a recent study on a large number of survivors found that BP was substantially higher in all diagnosis groups than expected on the basis of age-, sex-, race/ethnicity-, and BMI-specific population rates. 22,23 In conclusion, in the present study long-term sarcoma survivors previously treated with ifosfamide as the only nephrotoxic agent do not seem to be at high risk for nephrotoxicity. This finding has not been reported so far, it could be conditioned by the small number of cases, and further studies including a larger number of adult long-term survivors are required.…”
Section: Discussionsupporting
confidence: 46%
“…Therefore, all our patients were at the age at which common comorbidities such as diabetes and hypertension, which may contribute to further loss of nerve bers, are not common [18]. Furthermore, as has been shown many times, long-term ALL survivors are a high-risk group for developing diabetes [19] as well as hypertension [20]. For this reason, we hypothesized that the one-time screening with EP presented by us will allow to separate a group of patients at increased risk of developing clinically apparent visual, hearing or sensory impairment.…”
Section: Discussionmentioning
confidence: 93%
“…A separate 2017 study of greater than 3000 adult survivors suggested that these individuals face the same rates of hypertension as those who are approximately a decade older . Surprisingly, radiotherapy and chemotherapy were not found to be significantly associated with those increased rates.…”
Section: Cognitive Effects and Compounded Risksmentioning
confidence: 98%